Mineralogy and Provenance of Titanium-Vanadium Bearing Iron Sand Deposits from Purworejo-Kebumen, and Cilacap, Central Java - Teuku Ishlah; Martua Raja Parningotan; Rifi Sani Nugraha; Tatik Handayani; Hariro Zahra; Ernowo Ernowo (Journal of Mathematical and Fundamental Sciences)
This research aimed to find out the provenance, paleo weathering, tectonic environment, sediment maturity, and economic value of beach sand deposits in two study areas. The study areas were located on south coast of Purworejo-Kebumen and Cilacap, respectively. Ten representative samples were collected by hand auger and dried to reduce their water content, manually separating the magnetite concentrate using a 300-gauss magnet. The mineral composition and fraction were observed using a binocular microscope. Major oxide and trace elements concentrations were measured using the X-ray fluorescence and inductively coupled plasma mass spectrometry methods, respectively. The mineral assemblage consisted of pyroxene, amphibole, heavy minerals (hematite, ilmenite, and magnetite) and the light minerals found were quartz, plagioclase, and lithic fragments. The geochemical plot showed that all samples could be classified as greywacke, derived from mafic igneous provenance and were tectonically formed within an arc setting. The Chemical Index of Alteration showed an intensity of weathering as expected from tropical climates with weak weathering and the sediments are close to their source rock location. Fe2O3 had a positive correlation with TiO2 and V2O5; the iron sand from both areas has potential to be extracted, with iron, titanium, and vanadium as main commodities.